1998
DOI: 10.1074/jbc.273.49.32535
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for the 5-Oxo Class of Eicosanoids in Neutrophils

Abstract: 5-Hydroxy-and 5-oxo-eicosatetraenoate (5-HETE and 5-oxoETE) activate polymorphonuclear neutrophils (PMNs) through a common, receptor-like recognition system. To define this system, we examined the interaction of these eicosanoids with human PMNs. -20). The data imply that 5-HETE acts through a unique recognition system. However, evidence relating this system to receptor-like binding sites has proven difficult to obtain. Although PMNs process 5-HETE through various metabolic pathways (6 -8, 12, 21-23), one rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…GTP␥S inhibited the binding of both radioligands, whereas ATP␥S had no such effect (Table II). These results parallel those observed with partially purified plasma membranes from PMN (11). Since FMLP, C5a, PAF, and IL-8 did not displace 5-oxoETE binding to plasma membranes (11), and since LXA 4 and LXB 4 did not alter 5-oxoETE binding to mixed membranes (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…GTP␥S inhibited the binding of both radioligands, whereas ATP␥S had no such effect (Table II). These results parallel those observed with partially purified plasma membranes from PMN (11). Since FMLP, C5a, PAF, and IL-8 did not displace 5-oxoETE binding to plasma membranes (11), and since LXA 4 and LXB 4 did not alter 5-oxoETE binding to mixed membranes (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…These results parallel those observed with partially purified plasma membranes from PMN (11). Since FMLP, C5a, PAF, and IL-8 did not displace 5-oxoETE binding to plasma membranes (11), and since LXA 4 and LXB 4 did not alter 5-oxoETE binding to mixed membranes (Fig. 6), the 5-oxoETE binding site appears distinct from those for other granulocyte-stimulating eicosanoids and CF.…”
Section: Discussionsupporting
confidence: 75%
“…O'Flaherty andcoworkers (1995, 1996) reported that LTB 4 and 5-HETE had similar stimulatory activity in human neutrophils but the latter mediator had little affinity for BLT receptors and was resistant to BLT antagonists. These observations were extended by monitoring 3 H-labeled 5-oxo-ETE binding in PMN plasma membranes and demonstrating that specific binding sites for this radiolabel were not effected by other receptor ligands (O'Flaherty et al, 1998(O'Flaherty et al, , 2000. These results suggested a putative receptor for the oxoeicosanoids with the most potent native ligand being 5-oxo-ETE.…”
mentioning
confidence: 95%
“…This eicosanoid is known as a potent chemotactic factor of eosinophils and neutrophils (37)(38)(39)(40). O'Flaherty et al (41,42), and O'Flaherty and Rossi (43) had revealed that the chemotactic activity would be mediated through a pertussis toxin-sensitive GPCR. As a separate line of interesting studies on 5-oxo-ETE and the derivatives, Ghosh and Myers (44,45) had identified 5-oxo-ETE and 5-HETE as mitogenic as well as anti-apoptotic factors in prostate cancer cells.…”
Section: Fig 5 Effect Of 5-oxo-ete On Forskolin-stimulated Camp Promentioning
confidence: 99%